Development of nano hydroxyapatite loaded gellan gum nanocomposite scaffold for the regeneration of bone tissue affected by osteosarcoma - Huaidong Wang; Tao Bai; Mahani Yusoff; Nur Ain Atisya C.M. Khairuddin; Alina Irwana Muhamad A'srai; Mohd Hasmizam Razali (Results in Chemistry)
Advanced biomaterials play a critical role in promoting bone tissue engineering and regenerative medicine applications. This study aimed to fabricate a biomimetic scaffold incorporating nano-hydroxyapatite (nHA) and gellan gum (GG) for bone tissue repair. Nanocomposite scaffold loaded with nHA nanoparticles within a gellan gum matrix (nHA@GG) was successfully produced using a freeze-drying technique. Characterization by Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), and Scanning Electron Microscopy (SEM) corroborated the successful fabrication of the nHA@GG nanocomposite scaffold. XRD and FTIR analyses verified the phase composition and chemical bonding characteristics of hydroxyapatite, aligning with its successful formation within the scaffold. These findings highlight the potential of the nHA@GG nanocomposite scaffold to facilitate and accelerate apatite growth in in-vitro models. This might be attributed to the presence of nHA, which can act as a nucleation site for secondary apatite layer formation. The nHA@GG scaffold demonstrated efficient encapsulation and drug loading, with 35.48 ± 0.84 % encapsulation and 25.75 ± 0.75 % drug loading of sodium alendronate. The cumulative drug release of 38 % was achieved within 4 days. Furthermore, biocompatibility studies utilizing MC3T3 cells demonstrated significant cell proliferation (>100 %) and high cell viability (>90 %) on the nHA@GG scaffold. These findings, coupled with the favorable physicochemical properties and non-toxic nature of the nHA@GG scaffold, highlight its promising potential as a biomaterial for bone tissue regeneration.